2020
DOI: 10.1167/tvst.9.1.2
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Measurement of the Human Vitreous Chamber Volume Using Computed Tomography Imaging of 100 Eyes

Abstract: To accurately measure the vitreous chamber volume (VCV) in humans using high-resolution computed tomography (CT) scanning techniques combined with threedimensional analysis software. Potential relationships between age, axial length, and VCVs were also explored. Methods: In this retrospective study, the eyes of 100 healthy individuals were studied. Scans were acquired during clinical care and did not show any signs of orbital pathology. Exclusion criteria included any ocular history. CT scans were acquired wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 15 publications
2
21
0
1
Order By: Relevance
“…Nearly all subjects exhibited some degree of globe flattening (Table 1). However, the degree of globe flattening was relatively small when compared to the average reported vitreous chamber volume of 4650 and 4969 mm 3 in women and men, respectively [17], with an average volume displacement of 9.88 mm 3 (95% CI 4.56-15.19 mm 3 , p < 0.001) measured at R + 1 (Table 1 and black line in Fig. 2A).…”
Section: Resultsmentioning
confidence: 85%
“…Nearly all subjects exhibited some degree of globe flattening (Table 1). However, the degree of globe flattening was relatively small when compared to the average reported vitreous chamber volume of 4650 and 4969 mm 3 in women and men, respectively [17], with an average volume displacement of 9.88 mm 3 (95% CI 4.56-15.19 mm 3 , p < 0.001) measured at R + 1 (Table 1 and black line in Fig. 2A).…”
Section: Resultsmentioning
confidence: 85%
“…First, only a small part of the vitreous is sampled by the current scanning method. The theoretical area sampled is 5.9 mm by 1.5 mm, which represents only a small volume of the entire vitreous (estimated total volume 4.6–4.9 mm3) 13 and most of the anterior vitreous is unaccounted for. The distribution of VH along the axial length of the eye is not well understood, other than in certain uveitic entities (such as toxoplasmosis), which present with patches of VH directly overlying areas of focal chorioretinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the resolution is greater than that of traditional CT scanning. Azhdam et al [ 18 ] reported a study about the measurement of the vitreous volume using Computed Tomography Imaging. The mean vitreous volume in their study was 4649.97 mm 3 , larger than emmetropic group (4248.66 ± 358.12 mm 3 ) but small than pathological myopic group (8482.32 ± 677.44 mm 3 ) in our study.…”
Section: Discussionmentioning
confidence: 99%